Prospects and Challenges of Implementing Enterprise Mobility Management Case of a Large Telecom Service Provider in United Arab Emirates - Ali, Syed Mubashir; Usman, Muhammad (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Over the last few years, there has been an exponential rise in the trend to use mobile devices within enterprises. Organizations and employees are using their smart phones and tablets to aid in work. Several organizations has introduced the concept of â€œbring your own deviceâ€ (BYOD), in order to achieve more efficiency and improved productivity. This increase in use of mobile devices, although providing benefits to the organizations, is also resulting in more effort for the information technology (IT) staff to provide support and manage these devices within the enterprise. Several organizations around the globe are implementing mobile device management (MDM) / enterprise mobility management (EMM) solutions to manage mobile devices within the organization. This study identifies the prospects and challenges in implementing EMM using a case of a large telecom service provider in United Arab Emirates (UAE).